A John Hick Reader - Hick, J. author. aut Link
VIII, 200 p.
Keywords: John Hick is one of the most widely read and discussed living writers in modern theology and the philosophy of religion. This book offers students a one volume textbook on his thought. Extracts from his writings cover all the various themes for which Hick has become known: Faith and Knowledge, Philosophy of Religion, Evil and the God of Love, Death and Eternal Life, The Myth of God Incarnate, and Problems of Religious Pluralism. The extracts are preceded by an introductory essay by Paul Badham on John Hick's philosophical theology, and on the integrity of his life and thought.